An Approach for the Estimation of Concentrations of Soluble Compounds in E. coli Bioprocesses - Deividas Masaitis; Renaldas Urniezius; Rimvydas Simutis; Vygandas Vaitkus; Mindaugas Matukaitis; Benas Kemesis; Vytautas Galvanauskas; Benas Sinkevicius (Entropy, 2023)
Accurate estimations of the concentrations of soluble compounds are crucial for optimizing bioprocesses involving Escherichia coli (E. coli). This study proposes a hybrid model structure that leverages off-gas analysis data and physiological parameters, including the average biomass age and specific growth rate, to estimate soluble compounds such as acetate and glutamate in fed-batch cultivations We used a hybrid recurrent neural network to establish the relationships between these parameters. To enhance the precision of the estimates, the model incorporates ensemble averaging and information gain. Ensemble averaging combines varying model inputs, leading to more robust representations of the underlying dynamics in E. coli bioprocesses. Our hybrid model estimates acetates with 1% and 8% system precision using data from the first site and the second site at GSK plc, respectively. Using the data from the second site, the precision of the approach for other solutes was as fallows: isoleucine −8%, lactate and glutamate −9%, and a 13% error for glutamine., These results, demonstrate its practical potential.